Método de otimização estrutural para montagem de peças plásticas - Soken, Nestor Hidetomi [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Plastic parts present variations of form and dimension in relation to the mathematical model when manufactured by the injection process and, this variations can be predicted by specific CAE software as Moldflow, but the prediction is individual and unable to predict interferences, efforts, and tensions involved in the assembly process. To predict if the assembly process will occur accordingly to the specified conditions, tools are used to simulate the interactions of contact and force between the parts to be engaged. The softwares utilized to perform the simulations are commonly applied of insulated ways, however in this work the intent is to perform the structural optimizations in a recursive way predicting the limitations from productive process to avoid failures and non-conformities during the phases of empirical validation. The first virtual analysis using the Moldflow software, provides the mathematical model with the dimensional characteristics predicted by the simulation of the manufacturing process. The obtained model establishes the individual study of each plastic part in the end of the injection process, however the interactions between the two or more parts with these characteristics are unknown and can cause assemblies different from the desired project. Individually, the parts can achieve dimensions with the allowed tolerances in the project, but due to the unknown interactions, mainly referent to the assembly efforts, can cause unappropriated conditions to the final assembly. Therefore, there is a gap between manufacturing engineering and the validation phase, since the conformity verification of the assemblies composed by plastic parts is generally verified empirically, after the tooling construction for the pre-productive phase. The problems generated by this gap can be solved by using methods that... ( Complete abstract click electronic access below)

Peças plásticas apresentam variações de forma e dimensão em relação ao modelo matemático quando fabricadas pelo processo de injeção e, tais variações podem ser previstas por softwares CAE específicos como o Moldflow. Entretanto, esta previsão é individual e incapaz de prever interferências, esforços e tensões envolvidas no processo de montagem. Para prever se o processo de montagem ocorrerá dentro das condições especificadas, faz-se o uso de ferramentas para simular as interações de contato e forças entre as partes a serem acopladas. Os softwares utilizados para realizar as simulações são comumente usados de modos isolados, porém, neste trabalho o intuito é realizar otimizações estruturais de forma recursiva antevendo as limitações do processo produtivo para prevenir falhas e não conformidades em fases empíricas de validação. A primeira análise virtual utilizando-se o software Moldflow®, fornece o modelo matemático com as características dimensionais previstas pela simulação do processo de fabricação. O modelo obtido estabelece o estudo individual de cada peça plástica ao final do processo de injeção, porém as interações entre duas ou mais peças com tais características são desconhecidas e podem causar conjuntos montados diferentes daqueles projetados. Individualmente, as peças podem atingir dimensões dentro das tolerâncias permitidas em projeto, mas devido às interações desconhecidas, sobretudo referente aos esforços de montagem, podem gerar condições inapropriadas para o conjunto final. Portanto, existe uma lacuna entre o projeto na engenharia de manufatura e a fase de validação, sendo que a verificação de conformidade dos conjuntos constituídos por peças plásticas é verificada, geralmente de maneira empírica, após a confecção do ferramental para a fase ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Otimização estrutural; Processos de fabricação; Produtos industrializados; Simulação por computador; Manufacturing processes